Perilaku makan dan kejadian obesitas anak di SD Negeri Kota Kendari, Sulawesi Tenggara - Supiati Supiati; Djauhar Ismail; Retna Siwi P (Alma Ata University Press, 2014)
ABSTRACTBackground: Obesity is a health problem in developed countries as well as developing countries like Indonesia. National prevalence of overweight children aged 6-14 years is 9.5% in male and 6.4% in female. In Sulawesi Tenggara, there are 6.2% of male and 4.5% of female children who were overweight. Obesity in City of Kendari, there was an increase of obesity prevalence 0.15% in 2007 and 0.26% in 2008. Obesity can be influenced by various factors. It issuspected that eating behavior is a major factor, so we want to know, how big is the eating behaviors contribute to children’s obesity.Objectives: To determine the relationship of eating behavior and incidence of childhood obesity in one favorite public elementary school in Kendari Sulawesi Tenggara Province.Methods: This research was observational with cross sectional study design it was conducted in May 2010. Data was analysed using comparative test (chi square), and logistic regression.Results: There was significant correlation between eating behavior and obese incidence (p<0.01) with the power of prevalence ration (PR) was protective in their nature (PR= 1/0.12 = 8.3 In other words, the subject with healthy eating behavior had probability 8.3 times greater to not obese.Conclusions: There was significant correlation between diet behavior and the obesity in the children with the power of correlation and prevalence ratio was protective. The subject with healthy diet behavior had probability of 8.3 times to avoid obese incidence compared to the subject with non healthy eating behavior.KEYWORDS: eating behavior, obesity, elementary school childrenABSTRAKLatar belakang: Obesitas merupakan masalah kesehatan di negara maju dan berkembang seperti Indonesia. Prevalensi nasional berat badan lebih anak usia 6-14 tahun pada laki-laki 9,5% dan pada perempuan 6,4%. Di Sulawesi Tengggara, prevalensi tersebut 6,2% pada laki-laki dan 4,5% pada perempuan. Obesitas di Kota Kendari meningkat setiap tahun yaitu 0,15% pada tahun 2007 dan 0,26% tahun 2008. Obesitas dapat dipengaruhi oleh berbagai faktor, diduga perilaku makan merupakan faktor utama, sehingga ingin diketahui seberapa besar pengaruh perilaku makan menyumbang terhadap kejadian obesitas.Tujuan: Untuk mengetahui hubungan antara perilaku makan dan kejadian obesitas anak di SDN favorit Kota Kendari Provinsi Sulawesi Tenggara.Metode: Jenis penelitian ini adalah penelitian observasional dengan rancangan penelitian cross- sectional yang dilaksanakan pada bulan Mei 2010. Analisis data menggunakan uji komparatif (chi square), dan regresi logistik.Hasil: Ada hubungan terbalik antara perilaku makan dengan obesitas anak.P<0,01 dengan kekuatan hubungan dan rasio prevalensi (RP)=1/0,12=83, yaitu subjek yang mempunyai perilaku makan sehat mempunyai peluang 8,3 kali lebih besar untuk terhindar dari terjdinya obesitas.Kesimpulan: Ada hubungan yang sangat signifi kan antara perilaku makan dengan obesitas anak, dengan kekuatan hubungan dan rasio prevalensi yang bersifat protektif yaitu subjek yang mempunyai perilaku makan sehat mempunyai peluang 8,3 kali untuk terhindar dari terjadinya obesitas dibandingkan dengan anak yang berperilaku makan tidak sehat.KATA KUNCI: perilaku makan, obesitas, anak sekolah dasar